Sea-ice conditions in the Adélie Depression, Antarctica, during besetment of the icebreaker RV Xuelong. Issue 69 (2015) - Zhai, Mengxi; Li, Xinqing; Hui, Fengming; Cheng, Xiao; Heil, Petra; Zhao, Tiancheng; Jiang, Tianyu; Cheng, Cheng; Ci, Tianyu; Yan Liu; Chi, Zhaohui; Liu, Jian
Abstract: During the 30th Chinese Antarctic Expedition in 2013/14, the Chinese icebreaker RV Xuelong answered a rescue call from the Russian RV Akademik Shokalskiy . While assisting the repatriation of personnel from the Russian vessel to the Australian RV Aurora Australis, RV Xuelong itself became entrapped within the compacted ice in the Adélie Depression region. Analysis of MODIS and SAR imagery provides a detailed description of the regional sea-ice conditions which led to the 6 day long besetment of RV Xuelong . The remotely sensed imagery revealed four stages of sea-ice characteristics during the entrapment: the gathering, compaction, dispersion and calving stages. Four factors characterizing the local sea-ice conditions during late December 2013 and early January 2014 were identified: surface component of the coastal current; near-surface wind; ocean tides; and surface air temperature. This study demonstrates that shipping activity in ice-invested waters should be underpinned by general knowledge of the ice situation. In addition, during such activity high spatiotemporal resolution remotely sensed data should be acquired regularly to monitor local and regional sea-ice changes with a view to avoiding the besetment of vessels.